2006
DOI: 10.1021/bm0604808
|View full text |Cite
|
Sign up to set email alerts
|

Release of Plasmid DNA from Intravascular Stents Coated with Ultrathin Multilayered Polyelectrolyte Films

Abstract: Materials that permit control over the release of DNA from the surfaces of topologically complex implantable devices, such as intravascular stents, could contribute to the development of new approaches to the localized delivery of DNA. We report the fabrication of ultrathin, multilayered polyelectrolyte films that permit both the immobilization and controlled release of plasmid DNA from the surfaces of stainless steel intravascular stents. Our approach makes use of an aqueous-based, layer-by-layer method for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
236
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(259 citation statements)
references
References 68 publications
(221 reference statements)
13
236
4
Order By: Relevance
“…More recently, vectors have been immobilized in layers on surfaces using a technique termed polyelectrolyte layering [113][114][115][116]. Nanoscale films are created with alternating layers of negatively charged plasmid and positively charged polymers that are deposited on materials such as stainless steel stents [113][114][115][116].…”
Section: Vector Immobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, vectors have been immobilized in layers on surfaces using a technique termed polyelectrolyte layering [113][114][115][116]. Nanoscale films are created with alternating layers of negatively charged plasmid and positively charged polymers that are deposited on materials such as stainless steel stents [113][114][115][116].…”
Section: Vector Immobilizationmentioning
confidence: 99%
“…Nanoscale films are created with alternating layers of negatively charged plasmid and positively charged polymers that are deposited on materials such as stainless steel stents [113][114][115][116]. The duration of plasmid release can be manipulated through changing the degradability, conductivity, or electrochemistry of the polymer layers or substrate, while the released DNA is able to transfect cells without the aid of additional transfection agents [114,115]. Multilayered polyelectrolyte films have the ability to create highly tunable surfaces, and with the appropriate design of each layer, may potentially enable the sequential release of multiple gene sequences.…”
Section: Vector Immobilizationmentioning
confidence: 99%
“…Thus, several degradable multilayers of bio-polyelectrolytes, such as polysaccharides, polypeptides or polynucleotides have been reported by Picart et al [292]. Lynn et al [293][294][295][296][297][298][299][300][301] introduced poly α,β-aminoesters for the fabrication of capsules with degradable multilayers. Harashima et al [302] reported multifunctional envelope-type-nanocapsules including a nucleic acid core complex with polycations or lipid aggregates and also different polymeric shell structures equipped with specific functional groups binding ligand-targeted agents and cell-penetrating proteins.…”
Section: Polymer Micelles and Capsules Loaded With Fluorescent Therapmentioning
confidence: 99%
“…[7][8][9][10] These methods are entirely aqueous and permit nanometer-scale control over the structures of thin films fabricated from a wide variety of synthetic or natural polyelectrolytes, [7][8][9][10] [16][17][18][19][20] have demonstrated that it is possible to design multilayers that release DNA and promote surface-mediated cell transfection by fabricating films using DNA and cationic polymers that are hydrolytically, [12][13][14][15] enzymatically, [16,17] or reductively [18,19] degradable. Approaches to the fabrication, characterization, and application of DNAcontaining multilayers have been reviewed recently.…”
mentioning
confidence: 99%
“…[12][13][14] For these and all other experiments described below, films were fabricated on planar silicon substrates to permit characterization of film growth and erosion using ellipsometry. Figure 1 shows a plot of optical film thickness versus the number of polyamine/DNA layers (referred to hereafter as 'bilayers') deposited for films fabricated using either polymers 2a-d or unsubstituted PAH.…”
mentioning
confidence: 99%